2020
DOI: 10.1038/s41598-020-76051-z
|View full text |Cite
|
Sign up to set email alerts
|

Expanded and activated allogeneic NK cells are cytotoxic against B-chronic lymphocytic leukemia (B-CLL) cells with sporadic cases of resistance

Abstract: Adoptive transfer of allogeneic natural killer (NK) cells is becoming a credible immunotherapy for hematological malignancies. In the present work, using an optimized expansion/activation protocol of human NK cells, we generate expanded NK cells (eNK) with increased expression of CD56 and NKp44, while maintaining that of CD16. These eNK cells exerted significant cytotoxicity against cells from 34 B-CLL patients, with only 1 sample exhibiting resistance. This sporadic resistance did not correlate with match bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 46 publications
2
44
3
Order By: Relevance
“…Correlation analysis found that monocytes, neutrophils, NK cells resting, T cells CD4 memory resting, B cells memory, and mast cells activated were positively correlated with the risk score, and NK cells activated and T cells' follicular helper were negatively correlated with the risk score. Based on the results of the difference analysis and correlation analysis, we found that patients in the low-risk group had better long-term survival rates, which may be due to the high proportion of NK cells activated and T cells follicular helper (60)(61)(62). Most gene mutations were the initiating factor of tumorigenesis.…”
Section: Discussionmentioning
confidence: 93%
“…Correlation analysis found that monocytes, neutrophils, NK cells resting, T cells CD4 memory resting, B cells memory, and mast cells activated were positively correlated with the risk score, and NK cells activated and T cells' follicular helper were negatively correlated with the risk score. Based on the results of the difference analysis and correlation analysis, we found that patients in the low-risk group had better long-term survival rates, which may be due to the high proportion of NK cells activated and T cells follicular helper (60)(61)(62). Most gene mutations were the initiating factor of tumorigenesis.…”
Section: Discussionmentioning
confidence: 93%
“… 7 Regarding eNK cells obtained from PB, the significant increase in the NKp44 + population previously described in Sanchez-Martinez et al 40 was clearly confirmed in our latest study. 45 Consequently, we have determined the expression of NKp44 ligands on the surface of patient MM cells and found faint levels of expression (Suppl. Fig 3).…”
Section: Resultsmentioning
confidence: 99%
“…This result is in agreement with the reported low PD-1 expression in most eNK cells obtained from PB in our previous study. 45
Figure 3. A.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, allogeneic hematopoietic stem cell transplant (HSCT) and adoptive cell therapy with donor-derived, allogeneic NK cells ( Figure 2 ) are attractive alternatives to augment the graft-versus-tumor effect of NK cells generated by KIR mismatch [ 27 , 28 ]. While there are several studies observing the benefit of KIR-mismatched NK cells in leukemias [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ], more clinical and preclinical studies are needed to demonstrate the benefit of KIR mismatch in pediatric solid tumors. Delgado et al [ 20 ] found that osteosarcoma cell lines were most sensitive to allogeneic NK cell lysis when KIR receptor-ligand incompatibility was maximized.…”
Section: Nk Cell Activating and Inhibitory Receptorsmentioning
confidence: 99%